2020
DOI: 10.3390/app10062015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Graphene Oxide and Reduced Graphene Oxide as Blending Materials for Polysulfone and Polyvinylidene Difluoride Membranes

Abstract: Graphene is a single atomic plane of graphite, and it exhibits unique electronic, thermal, and mechanical properties. Exfoliated graphene oxide (GO) contains various hydrophilic functional groups, such as hydroxyl, epoxide, and carboxyl groups, that can modify the hydrophobic characteristics of a membrane surface. Though reduced graphene oxide (rGO) has fewer functional groups than GO, its associated sp2 structures and physical properties can be recovered. A considerable amount of research has focused on the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This is because an anatase phase for GO/TiO 2 thin film formed a better hydrophilic property. GO nanosheets are hydrophilic in nature because GO contains various hydrophilic functional groups [ 36 ]. However, the hydrophilic property of GO/TiO 2 thin film decreases after the addition of PEG, but slowly increases when the amount of PEG increases.…”
Section: Resultsmentioning
confidence: 99%
“…This is because an anatase phase for GO/TiO 2 thin film formed a better hydrophilic property. GO nanosheets are hydrophilic in nature because GO contains various hydrophilic functional groups [ 36 ]. However, the hydrophilic property of GO/TiO 2 thin film decreases after the addition of PEG, but slowly increases when the amount of PEG increases.…”
Section: Resultsmentioning
confidence: 99%
“…In another similar study, Ozcan et al also reported significant improvements in the material, brought by the addition of silica and GO nanohybrid particles [ 20 ]. Although reduced GO (rGO) has less functional groups compared with GO, its sp 2 structures and physical properties are still recoverable, and it is also purer and contains more graphene properties than GO [ 21 ]. Studies that have incorporated GO as a filler in the adhesive are abundant; however, limited data is available when it comes to the studies that have checked the efficacy of rGO filler particles in improving the adhesives’ mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of these functional groups indicates less sp2 bonding on the edge and basal plane of GO, resulting in a relatively high intensity of the D-band. Furthermore, based on the XPS results, the XPS spectra of C 1s for GO-S can be deconvoluted into three binding peaks: C-C bonding at 284 eV, C-O bonding at 286 eV, and C=O bonding at 288 eV (Figure 1(g)) [53,54]. Given the high level of functionalized groups and increased thickness, the XPS spectra of GO-S-0.5 show high-intensity peaks originating from the functional groups (at 284 and 286 eV) compared with GO-S-0.1, and the ratio of functional groups for GO-S-0.5 is 42.3%.…”
Section: Resultsmentioning
confidence: 99%